3d Enterprise (supernova sportswear store) - Isahak, Nur Eisya Natasya; Mohd Mazlan, Syahirah Sazlyn; Ahmad Khairulddin, Ahmad Hakim; Muhammad, Siti Nur Aishah; Onn, Nurul Atikah; Mohamad Sabri, Muhammad Hakim Syahmi (2021)
Supernova’s Sportswear Store is a new brand company and business that provides various types of cycling jerseys. On top of that, Supernova’s Sportswear Store also provides a small piece durable device on the suit called Integrated Microchip. Supernova has a new concept for anyone who wishes to wear it, especially cyclists. Supernova’s Sportswear Store is located in Jalan PKSA Taman Perindustrian Krubong, Melaka. Our business will be located at NO 6C-1 TINGKAT 1, JALAN PKSA TAMAN PERINDUSTRIAN KRUBONG, 75200 MELAKA, MELAKA. The reason why we build up our store at this location is because it will be the most suitable place and strategic place to open and run a new business. This location is crowded by a lot of local residents of Melaka and tourists from other states and country. Our target customer will be the resident of Melaka and the tourists from other states and country because the location Krubong is one of the well- known places for tourists to visit. We picked these target customer as they will help us to expand the business widely and give us many opportunities to promote our jersey in Krubong, Melaka. Our company organization consists of Board of Director which are the head of the company, General Manager that responsible in managing the company, Financial Department which responsible with our financial management, System Integration Department, Sales & Marketing Department and Technology Department.